Pseudo Hemifacial Microsomia With Condylar-Coronoid Collapse: New Therapeutic Approach in Growing Patients. Issue 8 (November 2020) - Perrotta, Stefania; Bocchino, Tecla; D'Antò, Vincenzo; Michelotti, Ambrosina; Valletta, Rosa
Abstract : Abstract: The purpose of this study is to describe the management of 2 dimorphic patients affected by Hemimandibular Hypoplasia with Condylar-Coronoid Collapse (HH-CCC), also called Pseudo Hemifacial Microsomia, where the orthopedic treatment gave an excellent long-term follow-up. The patients were a 7-year-old female and a 6-year-old male with a HH-CCC on the left side, an asymmetrical face with chin deviation, class II dental malocclusion and canting of the occlusal plane. An X-ray evaluation and clinical observation confirmed the unilateral mandibular deficiency and the collapse of the condyle on the coronoid process on the affected side. The treatment plan consisted of the use of an asymmetrical functional appliance with a vertical screw. The appliance was gradually activated on the vertical plane on one side by a screw incorporated on an acrylic plate. It was used for 22 hours/day, including sleep time but not during meals. This treatment improved the patient' s facial appearance. HH-CCC showed a positive response to functional therapy.